2020
DOI: 10.1108/nfs-03-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa ethanolic extract modulates adipokine levels, decreases visceral fat and improves glycemic profile in high-fat/sugar diet-induced obese rats

Abstract: Purpose The purpose of this study is to evaluate the effect of Hibiscus sabdariffa ethanolic extract (HsE) on protein levels of tumor necrosis factor (TNF)-α, interleukin (IL)-6, adiponectin and leptin in adipose tissue, as well as on the lipid and glycemic profiles of high-fat/sugar diet-induced obese (DIO) rats. Design/methodology/approach Obesity was induced in male Wistar rats through a high-fat/sugar diet provided for eight weeks. Control rats received a standard diet. The high-fat/sugar DIO animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Other authors have also reported the effect of Hibiscus and Lemon verbena on some of the analyzed hormones, such as Hibiscus on leptin expression [ 27 ], or Lemon verbena activating AMPK [ 28 ], which is known to have an important role in controlling appetite in the hypothalamus [ 29 ]. Furthermore, high polyphenolic intake has been associated with weight loss, particularly anthocyanins and flavonols [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have also reported the effect of Hibiscus and Lemon verbena on some of the analyzed hormones, such as Hibiscus on leptin expression [ 27 ], or Lemon verbena activating AMPK [ 28 ], which is known to have an important role in controlling appetite in the hypothalamus [ 29 ]. Furthermore, high polyphenolic intake has been associated with weight loss, particularly anthocyanins and flavonols [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, recent research seems to have granted special interest for the search of effective natural glucosidase and lipase inhibitors (Hamden et al, 2017). Previous research studies have shown that medicinal plants exhibited pronounced inhibitory effects towards the activities of a-amylase, lipase and inflammation (Kang et al, 2015;Ghasemian et al, 2016;Von Dentz, et al, 2020;Joshi et al, 2018;Feng et al, 2020;Mohamed et al, 2020;Tiss et al, 2020). In fact, Plants are a source of bioactive secondary metabolites such as glycosides, saponins, flavonoids, steroids, tannins, alkaloids and terpenes, which act as strong antioxidant to protect body from oxidative damage (Upreti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…11 High-calorie-diet-induced obesity resulted in increased weight and body fat corroborating other studies conducted in the same laboratory. 15 The ET protocols used in this study were effective in reducing body weight and fat. Body weight decreased 10% and 25% in normal-weight and obese rats after 60 days of ET, respectively.…”
Section: Discussionmentioning
confidence: 81%
“…The ET protocol was established for each group according to their clinical conditions. 15 In a pilot study, obese rats could not perform interval training due to excess weight. Thus, moderate intensity AT was used for them (50% of Speed max in the MPET).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation